Application of Markov chain model in determining drought proneness (MAUSAM, 1984)
Rainfall distribution especially run of wet and dry spells will have dominating effect on the crop yield. Two state Markov chain model of order one has been used to evaluate sequences of dry and wet weeks during southwest monsoon period over dry farming tract of Maharashtra. An index based on parameters of this model has been developed to bring out the degree of drought proneness. Following this index dry farming tract of Maharashtra has been delineated into five zones of different degree of drought proneness.